2018
DOI: 10.22146/jpti.28886
|View full text |Cite
|
Sign up to set email alerts
|

Potensi Parasitoid Telur dalam Mengendalikan Wereng Batang Cokelat (Nilaparvata lugens Stal.) Pasca Ledakan Populasi di Kabupaten Banyumas

Abstract: This study aims to determine the type and potency of egg parasitoid in controlling brown planthopper (Nilaparvata lugens Stal.) pests in Banyumas regency after the pest’s explosion. This research has been conducted in five districts of the endemic area of brown planthopper in Banyumas Regency, i.e. in  Jatilawang, Cilongok, Kebasen, Sumpiuh, and Kembaran. Each of the  districts was taken 5 sample villages. The testing and calculation of the level of parasitization  were done in the laboratory of Plant Protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…Siklus hidup N. lugens Stål. tidak terputus selama masa penanaman disebabkan oleh pemilihan pola penanaman tidak serempak oleh petani (Minarni, et al, 2018). Berdasarkan pengamatan Safitri dan Yulianto (2019) alasan yang paling sering digunakan petani dalam menerapkan pola penanaman tidak serempak ialah kondisi air lahan yang kurang mencukupi, kondisi lahan seperti kemiringan dan ketinggian, sarana prasarana yang kurang memadai, tenaga kerja yang terbatas serta pengejaran waktu tanam oleh petani itu sendiri.…”
Section: Pendahuluanunclassified
“…Siklus hidup N. lugens Stål. tidak terputus selama masa penanaman disebabkan oleh pemilihan pola penanaman tidak serempak oleh petani (Minarni, et al, 2018). Berdasarkan pengamatan Safitri dan Yulianto (2019) alasan yang paling sering digunakan petani dalam menerapkan pola penanaman tidak serempak ialah kondisi air lahan yang kurang mencukupi, kondisi lahan seperti kemiringan dan ketinggian, sarana prasarana yang kurang memadai, tenaga kerja yang terbatas serta pengejaran waktu tanam oleh petani itu sendiri.…”
Section: Pendahuluanunclassified
“…Different genera of egg parasitoids have been reported in Indonesia. For example, Minarni et al (2018) reported Gonatocerus sp. dan Oligosita sp.…”
Section: Parasitoids Of N Lugens Eggsmentioning
confidence: 99%
“…Since there are various types of pesticides available in the market, farmers tend to mix several pesticides expecting higher effects of the applied pesticides. Such erroneous practices finally become regular habit regardless the presence of the pests (Minarni, Suyanto, & Kartini, 2018).…”
Section: The Impact Of Insecticides Application In Rice Fieldmentioning
confidence: 99%